2011
DOI: 10.1007/s11164-011-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphology control of TiO2 through hydrothermal synthesis method using protonic tetratitanate

Abstract: Fibrous TiO 2 and plate-like TiO 2 were obtained through the hydrothermal synthesis method by using two kinds of protonic tetratitanate (H 2 Ti 4 O 9 ), prepared by ion exchange of K 2 Ti 4 O 9 and HCl, or milled K 2 Ti 4 O 9 and HCl, respectively. The product made by hydrothermal treatment of H 2 Ti 4 O 9 without milling in water consisted of anatase TiO 2 and retained the fibrous morphology of the precursor but with fine crystals attached on the surface, formed by the in situ topotactic transformation reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this paper, we report the work by using the precursor of nanoribbons exfoliated from layered tetratitanate. The crystal phases and morphologies of the TiO 2 obtained were different from those obtained through hydrothermal/solvothermal treatments on the protonated tetratitanate. Anatase nanocrystals with different exposed facets were controllably achieved, and after tuning the reactive temperature, the nanocrystals with different sizes and shapes were also controllably achieved by microwave-assisted hydrothermal treatment. The possible formation mechanism of the anatase nanocrystals and the photocatalytic activities and photovoltaic performances are investigated.…”
Section: Introductionmentioning
confidence: 94%
“…In this paper, we report the work by using the precursor of nanoribbons exfoliated from layered tetratitanate. The crystal phases and morphologies of the TiO 2 obtained were different from those obtained through hydrothermal/solvothermal treatments on the protonated tetratitanate. Anatase nanocrystals with different exposed facets were controllably achieved, and after tuning the reactive temperature, the nanocrystals with different sizes and shapes were also controllably achieved by microwave-assisted hydrothermal treatment. The possible formation mechanism of the anatase nanocrystals and the photocatalytic activities and photovoltaic performances are investigated.…”
Section: Introductionmentioning
confidence: 94%
“…Precise control of the synthesis technique is crucial for improving the properties of these materials. Several liquid-phase syntheses, including coprecipitation, hydro/solvothermal, and sol–gel methods, have been developed to synthesize submicrocrystals and nanocrystals. Due to its interesting structural and optical features, AEu­(MoO4)­2 has been extensively studied as a phosphor material. , ,,,,, Among these methods, hydrothermal synthesis stands out as one of the most effective “soft chemistry” techniques because it can proceed under mild conditions to obtain crystals. In contrast, coprecipitation and sol–gel methods often require high-temperature treatments to crystallize the particles.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrothermal method is highly advantageous in this regard. Under hydrothermal synthesis conditions, morphology and particle size can be easily controlled by parameters such as temperature, solution pH, organic cosolvent, and the molar ratio of raw materials. ,,,,, Additionally, Wu et al reported that the relationship between morphology and luminescence properties of KEu­(MoO 4 ) 2 leads to improved luminescence intensity due to uniform morphology, larger particle size, and preferred orientation . Despite numerous references on morphology control of phosphor materials using the hydrothermal method, there is a lack of literature reporting the relationship between crystal growth, which produces specific morphologies, and luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the technology and devices required to carry out this synthesis methods is reasonably priced and relatively easy to use. Currently, there is a tendency to improve the synthesis conditions in order to manipulate the morphology, dimensions and crystalline preferential orientation of the synthesized nanomaterials [11][12][13][14][15][16][17] which have a direct impact on the properties of the products.…”
Section: Introductionmentioning
confidence: 99%